A Comparison between Fiber Reinforced and Hybrid Composite - Motaz A. Ghulman,; Mohamed T. Hamed,; Abdulghani I. Mira,; Ghada H. Naguib,; Abeer M. Alnowaiser, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The problem of fracture of composite resin under flexure and shear loads has regularly been encountered. Few studies claimed that the addition of fiber improves the mechanical properties of dental composite. The aim of this study was to evaluate the effect of the addition of polyethylene fiber to hybrid composite on the following properties; water sorption, compressive strength, flexural strength, shear bond strength to enamel, and shear bond strength to dentin. A total number of 100 specimens were used to conduct this study. The results were collected, tabulated and statistically analyzed using ANOVA and students "t" test. It was found that the addition of polyethylene fiber resulted in a significant increase in the water sorption and in the flexure strength properties of hybrid composite (p < 0.05). It was concluded that the addition of polyethylene fiber does not significantly improve the properties of hybrid composite, and further studies are required to evaluate the effectiveness of adding fiber to hybrid composite.